Reassessment of the Phylogeny and Systematics of Chinese Parnassia (Celastraceae): A Thorough Investigation Using Whole Plastomes and Nuclear Ribosomal DNA - Xia, Ming-Ze; Li, Yan; Zhang, Fa-Qi; Yu, Jing-Ya; Khan, Gulzar; Chi, Xiao-Feng; Xu, Hao; Chen, Shi-Long (Frontiers in Plant Science, 2022)
Parnassia L., a perennial herbaceous genus in the family Celastraceae, consists of about 60 species and mainly distributed in the Pan-Himalayan and surrounding mountainous regions. The taxonomic position and phylogenetic relationships of the genus are still controversial. Herein, we reassessed the taxonomic status of Parnassia and its intra and inter-generic phylogeny within Celastraceae. To that end, we sequenced and assembled the whole plastid genomes and nuclear ribosomal DNA (nrDNA) of 48 species (74 individuals), including 25 species of Parnassia and 23 species from other genera of Celastraceae. We integrated high throughput sequence data with advanced statistical toolkits and performed the analyses. Our results supported the Angiosperm Phylogeny Group IV (APG IV) taxonomy which kept the genus to the family Celastraceae. Although there were topological conflicts between plastid and nrDNA phylogenetic trees, Parnassia was fully supported as a monophyletic group in all cases. We presented a first attempt to estimate the divergence of Parnassia, molecular clock analysis indicated that the diversification occurred during the Eocene. The molecular phylogenetic results confirmed numerous taxonomic revisions, revealing that the morphological characters used in Parnassia taxonomy and systematics might have evolved multiple times. In addition, we speculated that hybridization/introgression might exist during genus evolution, which need to be further studied. Similarly, more in‐depth studies will clarify the diversification of characters and species evolution models of this genus.